MANAGEMENT NUTRITION FULFILLMENT OF NON CASH FOOD ASSISTANCE (BPNT) - Syahrir, Sukfitrianty; Syarfaini, Syarfaini; Nildawati, Nildawati; Berlian, Berlian; Iriyani Harun; Aswady; Astuti Nur (Homes Journal: Hospital Management Studies Journal, 2024)
Backround: The Non-Cash Food Assistance Program (BPNT) is a type of direct community assistance to provide basic necessities with the aim of allowing people to consume better food and nutrition. Objective: This study aims to management nutrition fullfillment of Non Cash Food Assitance (BPNT). Method: This research usesmix method. The population in this study were all households receiving the Gowa Regency Non-Cash Food Assistance Program (BPNT). Result: In this research, recipients of non-cash food assistance (BPNT) have utilized family food access assistance by >50% or around 329 people, and there are still 21 people (4.64%) who have not maximized BPNT for family food access. 100% of recipients receive BPNT of <Rp. 300,000/month and allocate <Rp. 300,000 for purchasing food/food. Conclusion: Basically, the distribution of BPNT in Gowa Regency has an impact on improving welfare and fulfilling the economy as well as meeting basic needs, especially food.